Pressure-temperature evolution of primordial solar system solids during impact-induced compaction - Bland, Phil; Collins, G.; Davison, T.; Abreu, N.; Ciesla, F.; Muxworthy, A.; Moore, J. (Nature Publishing Group, 2014)
Prior to becoming chondritic meteorites, primordial solids were a poorly consolidated mix of mm-scale igneous inclusions (chondrules) and high-porosity sub-μm dust (matrix). We used high-resolution numerical simulations to track the effect of impact-induced compaction on these materials. Here we show that impact velocities as low as 1.5 km s−1 were capable of heating the matrix to >1,000 K, with pressure–temperature varying by >10 GPa and >1,000 K over ~100 μm. Chondrules were unaffected, acting as heat-sinks: matrix temperature excursions were brief. As impact-induced compaction was a primary and ubiquitous process, our new understanding of its effects requires that key aspects of the chondrite record be re-evaluated: palaeomagnetism, petrography and variability in shock level across meteorite groups. Our data suggest a lithification mechanism for meteorites, and provide a ‘speed limit’ constraint on major compressive impacts that is inconsistent with recent models of solar system orbital architecture that require an early, rapid phase of main-belt collisional evolution.